P499 A comparison of health-related quality of life in nurse-led vs. conventional inflammatory bowel disease follow-up. (16th January 2018) - Alvestad, L; Jelsness-Jørgensen, L -P; Goll, R; Clancy, A; Valle, P C; Broderstad, A R
Abstract: Background: Inflammatory bowel disease (IBD), consisting of Crohn's disease (CD) and ulcerative colitis (UC), are chronic disorders known to have a considerable negative impact on health-related quality of life (HRQoL). Specialist nurses have been increasingly involved in the follow-up management of IBD patients by having a consultative and coordinating role, closely cooperating with gastroenterologists. Whether the patients HRQoL differs between nurse-led and conventional follow-up is however, relatively unknown. The aim of this study was thus to compare two different follow-up regimes with respect to patients HRQoL: nurse-led follow-up (NF) vs. conventional-follow-up (CF). Methods: In this cross-sectional, multicentre study, a total of 312 participants, aged 18–80 years, were included. HRQoL was assessed by a single time point measurement of the Norwegian version of the Inflammatory Bowel Disease Questionnaire (N-IBDQ). A one-way between-group analysis of covariance was conducted to compare the mean score in N-IBDQ including sub scores for each domain, adjusted for diagnoses, age and sex. The total possible score is 32–224, with a higher score indicating better quality of life. An absolute distinction of 16 points define a minimal clinically important difference in the N-IBDQ total score. The data were analysed using SPSS statistics 24. All tests were two-sided with a 95% confidence interval. Results: The current results are based on preliminary data from 244 participants. There were no statistically significant differences with regard the N-IBDQ total mean score, between those recruited from the NF – model n = 140 or CF–model n = 104. N-IBDQ total score values were mean 176.17 (CI: 171.06–181. 27) and mean 168.36 (CI: 162.37–174.36) in NF and CF, respectively. N-IBDQ subscale scores displayed statistically significant differences in two domains, bowel function 1: NF mean 41.33 (CI: 40.04–42.62) and CF mean 39.24 (CI: 37.72–40.75) ( p = 0.047), and social function: NF mean 24.53 (CI: 23.70–25.36) and CF mean 22.88 (CI: 21.91–23.86) ( p = 0.015). In the remaining three N-IBDQ subscales, no statistically significant differences were observed. Conclusions: In this study, significant differences were detected for the Bowel function 1 and Social functions subscales of the N-IBDQ. However, the analyses indicate no overall significant differences in self-reported HRQoL in the nurse-led follow-up vs. conventional-follow-up.